Robotic touch shifts perception of embodiment to a prosthesis in targeted reinnervation amputees - Marasco, Paul D.; Kim, Keehoon; Colgate, James Edward; Peshkin, Michael A.; Kuiken, Todd A. (OXFORD UNIV PRESS, 2011)
Existing prosthetic limbs do not provide amputees with cutaneous feedback. Tactile feedback is essential to intuitive control of a prosthetic limb and it is now clear that the sense of body self-identification is also linked to cutaneous touch. Here we have created an artificial sense of touch for a prosthetic limb by coupling a pressure sensor on the hand through a robotic stimulator to surgically redirected cutaneous sensory nerves (targeted reinnervation) that once served the lost limb. We hypothesize that providing physiologically relevant cutaneous touch feedback may help an amputee incorporate an artificial limb into his or her self image. To investigate this we used a robotic touch interface coupled with a prosthetic limb and tested it with two targeted reinnervation amputees in a series of experiments fashioned after the Rubber Hand Illusion. Results from both subjective (self-reported) and objective (physiological) measures of embodiment (questionnaires, psychophysical temporal order judgements and residual limb temperature measurements) indicate that returning physiologically appropriate cutaneous feedback from a prosthetic limb drives a perceptual shift towards embodiment of the device for these amputees. Measurements provide evidence that the illusion created is vivid. We suggest that this may help amputees to more effectively incorporate an artificial limb into their self image, providing the possibility that a prosthesis becomes not only a tool, but also an integrated body part.
Keywords: MASSIVE CORTICAL REORGANIZATION; PRIMARY SOMATOSENSORY CORTEX; SENSORY-FEEDBACK-SYSTEM; UPPER-LIMB AMPUTEES; TRANSHUMERAL AMPUTEES; MACHINE INTERFACE; RUBBER HAND; CHEST SKIN; BODY; OWNERSHIP